Characterization of Vitellogenin and Vitellogenin Receptor of Conopomorpha sinensis Bradley and Their Responses to Sublethal Concentrations of Insecticide - Yao, Qiong; Xu, Shu; Dong, Yizhi; Que, Yinli; Quan, Linfa; Chen, Bingxu (Frontiers in Physiology, 2018)
Conopomorpha sinensis Bradley is the dominant borer pest of Litchi chinesis and Euphoria longan. Current management of C. sinensis relies upon insecticide application to adult moths. In addition to the direct mortality induced by insecticides, a sublethal dose of insecticides also affects growth, survival and reproduction in the exposed insects. Vitellogenin (Vg) and vitellogenin receptor (VgR) are normally identified as essential reproduction-related proteins in insects. In this study, we characterized these two genes from C. sinensis, and investigated their differential responses to sublethal concentrations of insecticide. Cloned CsVg and CsVgR consist of 5391 and 5424-bp open reading frames, which encode proteins of 1796 and 1807 amino acid residues, respectively. The CsVg protein contains the typical vitellogenin, DUF1943 and VWFD domains as other reported lepidopteran Vgs. The CsVgR was characterized as a typical low density lipoprotein receptor with 2 highly conserved LBD and EGF precursor domains, one hydrophobic transmembrane domain, one cytoplasmic domain, and 13 putative N-glycosylation sites. We next assessed the sublethal effect of four major insecticides on egg-laying in C. sinensis. The toxicity against C. sinensis varied among the insecticides tested, with LC50 values ranging from 0.23 ppm for chlorpyrifos to 20.00 ppm for β-cypermethrin, among which emamectin benzoate (EB) showed a significant negative impact on egg-laying, survival rate, ovarian development, and mating rate of C. sinensis at LC30 doses. Further investigation showed that the transcriptional level of CsVg and CsVgR were impaired in different way at 24 h, 48 h and 72 h after EB exposure, and this result was in agreement with the diminished egg-laying of C. sinensis in the sublethal concentration EB-treated group. A repressed transcription level of CsVgR was observed at 48 h after treatment, suggesting that EB elicits a delayed response in the abundance of CsVgR. These results established different roles of CsVg and CsVgR in response to the sublethal effect of insecticides. CsVg might be a better parameter than CsVgR for assessing the effect of sublethal insecticides on reproduction in C. sinensis.